TISSUE CELL INTEGRITY IS AN IMPORTANT DETERMINANT TO PREDICT MUSCLE STRENGTH IN PATIENT IN POST STROKE REHABILITATION - Michael Knops; Nicole Ebner; Nadja Scherbakov; Kristina Norman; Claudia Doehner; Artur Nosul; Stephan von Haehling; Michael Joebges; Wolfram Doehner (The Korean Society of Nephrology, 2012)
Physical disability is a common result and a major complication after stroke. The skeletal muscle is the main effector organ accountable for this disability. Yet, metabolic, structural and functional impairment of muscle tissue are not recognized as potential targets to improve post-stroke rehabilitation and remobilisation. We aimed to investigate metabolic and structural characteristics of the lean tissue as predictors of muscle function in patients after acute stroke. We studied 40 patients (age 68±12y, BMI 27±4, mean±SD) at the beginning of post-stroke hospitalized rehabilitation. All patients had paretic or plegic deficits of the limb due to acute stroke. Maximum isometric handgrip strength was measured in the stronger / non-paretic arm by a dynamometer. Lean tissue characteristics were assessed by whole body impedance analyses (BIA). Resistance (tissue hydratation, R/H) and reactance (cell integrity, Xc/H) were assessed and phase angle (phase-α) vector analyses were performed to evaluate lean tissue quality. Patients were grouped into tertials for muscle strength (hand grip in tertial 1/2/3: 17.07±4.10 N / 28.33±2.84 N / 41.21±7.97 N). Tertials were similar for BMI and age. Lean tissue quality measures increased stepwise with muscle strength tertials (phase-α in tertial 1/2/3: 4.28±0.84 / 4.80±1.06 / 5.51±0.91; ANOVA p=0.0064). Univariable regression analysis showed a significant association between muscle strength and tissue structure characteristics (R/H: r=0.48, p=0.0016; phase-α: r=0.55, p=0.0002). After multivariable adjustment for age and BMI, R/H and phase-α remained significant predictors of muscle strength (R/H: joint r=0.65, p=0.0009; phase-α: joint r=0.65, p=0.0009). In conclusion, poor lean tissue quality is a major determining factor to predict muscle strength in patients after stroke. Body impedance is an easy applicable tool to evaluate tissues metabolic and structural characteristics during post-stroke rehabilitation. BIA assessments may be helpful to support the rehabilitation process of patients after stroke by stressing the aspects of tissue quality.